Does filter-aided sample preparation provide sufficient method linearity for quantitative plant shotgun proteomics? - Leonova, Tatiana; Ihling, Christian; Saoud, Mohamad; Frolova, Nadezhda; Rennert, Robert; Wessjohann, Ludger A.; Frolov, Andrej (Frontiers in Plant Science, 2022)
Due to its outstanding throughput and analytical resolution, gel-free LC-based shotgun proteomics represents the gold standard of proteome analysis. Thereby, the efficiency of sample preparation dramatically affects the correctness and reliability of protein quantification. Thus, the steps of protein isolation, solubilization and proteolysis represent the principal bottle neck of shotgun proteomics. The desired performance of the sample preparation protocols can be achieved by application of detergents. However, these compounds ultimately compromise reverse phase chromatographic separation and disrupt electrospray ionization. Filter aided sample preparation (FASP) represents an elegant approach to overcome these limitations. Although this method is comprehensively validated for cell proteomics, its applicability to plants and compatibility with plant-specific protein isolation protocols is still to be confirmed. Thereby, the most important gap is the absence of the data on the linearity of underlying protein quantification methods for plant matrices. To fill this gap, we address here the potential of FASP in combination with two protein isolation protocols for quantitative analysis of pea (Pisum sativum) seed and Arabidopsis thaliana leaf proteomes by the shotgun approach. For this aim, in comprehensive spiking experiments with bovine serum albumin (BSA), we evaluated the linear dynamic range (LDR) of protein quantification in the presence of plant matrices. Further, we addressed the interference of two different plant matrices in quantitative experiments, accomplished with two alternative sample preparation workflows in comparison to conventional FASP-based digestion of cell lysates, considered here as a reference. The spiking experiments revealed high sensitivities (LODs of up to 4 fmol) for spiked BSA and LDRs of at least 0.6 x 102. Thereby, phenol extraction yielded slightly better recoveries, whereas the detergent-based method showed better linearity. Thus, our results indicate very good applicability of FASP to quantitative plant proteomics with only limited impact of the protein isolation technique on the methods overall performance.